Rare Copy Number Variants in Isolated Sporadic and Syndromic Atrioventricular Septal Defects - Priest, James R (Wiley Subscription Services, Inc., A Wiley Company, 2012)
Atrioventricular septal defects (AVSDs) are a frequent but not universal component of Down syndrome (DS), while AVSDs in otherwise normal individuals have no well-defined genetic basis. The contribution of copy number variation (CNV) to specific congenital heart disease (CHD) phenotypes including AVSD is unknown. We hypothesized that de novo CNVs on chromosome 21 might cause isolated sporadic AVSDs, and separately that CNVs throughout the genome might constitute an additional genetic risk factor for AVSD in patients with DS. We utilized a custom oligonucleotide arrays targeted to CNV hotspots that are flanked by large duplicated segments of high sequence identity. We assayed 29 euploid and 50 DS individuals with AVSD, and compared to general population controls. In patients with isolated-sporadic AVSD we identified two large unique deletions outside of chromosome 21 not seen in the expanded set of 8,635 controls, each overlapping with larger deletions associated with similar CHD reported in the DECIPHER database. There was a small duplication in one patient with DS and AVSD. We conclude that isolated sporadic AVSDs may be occasionally associated with large de novo genomic structural variation outside of chromosome 21. The absence of CNVs on chromosome 21 in patients with isolated sporadic AVSD suggests that sub-chromosomal duplications or deletions of greater than 150 kbp on chromosome 21 do not cause sporadic AVSDs. Large CNVs do not appear to be an additive risk factor for AVSD in the DS population. © 2012 Wiley Periodicals, Inc.